A midsummer night's dream - Chan, Crystal S. (Manga classics., 2018)
Presents a manga-style adaptation of William Shakespeare's "A Midsummer Night's Dream," in which the King and Queen of the Fairies quarrel and everyone around them, fairy and human alike, suffers for it.